2022
DOI: 10.1002/pc.27173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wet treatment on bonding strength and electrothermal performance of electrothermal plywood bonded with emulsion polymer‐isocyanate adhesive

Abstract: To create a green, safe, and aldehyde-free indoor heating environment, an eco-friendly emulsion polymer-isocyanate (EPI) adhesive was applied to the preparation of electrothermal plywood with built-in carbon fiber paper. The optimized process parameters of electrothermal plywood were 0.9 MPa, 120 C, 6 min, and 200 g/m 2 for hot-pressing pressure, temperature, time, and glue spread amount, respectively. After water immersion for 24 h, the bonding strength of wet-treated electrothermal plywood decreased to 0.89 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Heaters are heat-transferring devices that are commonly used in cold weather, chilly areas, and for many more heat-transferring applications, [1][2][3][4] where conductive heaters take the electrical energy as input and convert it into heat energy as output. 3,[5][6][7][8][9] Generally, conductive heaters possess different configurations, such as linear and twodimensional (2D) configuration, 10,11 that exhibits different input and output powers. The filament-type heater has a linear configuration, whereas the sheet-type heater possesses two-dimensional (2D) configuration that exhibits easy control and uniform heating on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heaters are heat-transferring devices that are commonly used in cold weather, chilly areas, and for many more heat-transferring applications, [1][2][3][4] where conductive heaters take the electrical energy as input and convert it into heat energy as output. 3,[5][6][7][8][9] Generally, conductive heaters possess different configurations, such as linear and twodimensional (2D) configuration, 10,11 that exhibits different input and output powers. The filament-type heater has a linear configuration, whereas the sheet-type heater possesses two-dimensional (2D) configuration that exhibits easy control and uniform heating on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Heaters are heat‐transferring devices that are commonly used in cold weather, chilly areas, and for many more heat‐transferring applications, 1–4 where conductive heaters take the electrical energy as input and convert it into heat energy as output 3,5–9 . Generally, conductive heaters possess different configurations, such as linear and two‐dimensional (2D) configuration, 10,11 that exhibits different input and output powers.…”
Section: Introductionmentioning
confidence: 99%
“…X. Tao et al (2023) identified an environmentally friendly emulsion polymer-isocyanate (EPI) adhesive that was used to prepare electrothermal plywood with embedded carbon fibre paper. The authors established that wet treatment has a substantial effect on the joint strength and electrothermal performance of electrothermal plywood bonded with an emulsion polymer-isocyanate adhesive.…”
Section: Introductionmentioning
confidence: 99%